'You have to be mindful of whose story it is': The challenges of undertaking life story work with people with dementia and their family carers. (March 2015) - McKeown, Jane; Ryan, Tony; Ingleton, Christine; Clarke, Amanda
Introduction: Life story work is increasingly being used with people with dementia; this work offers a critical appraisal of some challenges that may be faced in practice. Design and methods: An in-depth case study analysis was undertaken to understand the experiences of people with dementia, family carers and care staff in using life story work in an NHS Mental Health and Social Care Trust. Data collection included semi-structured interviews, observation, conversations and field notes. Findings: Private memories were sometimes recalled by the person with dementia that were not for inclusion in any written product; enabling the person with dementia to tell their own life story could be a challenge; quality of the life story books was variable and; at times, life story work may be overused with the person with dementia. Conclusion: Services should not be deterred from undertaking life story work with people with dementia, but there is a need to adopt a planned approach to its implementation that includes facilitation, education and supervision.